Parenting behaviours of mothers living in the east of Turkey in the postpartum period - Aynur AYTEKİN ÖZDEMİR; Semra KÖSE; Sibel KÜÇÜKOĞLU; Sevda AKBAKAY (Anadolu Hemşirelik ve Sağlık Bilimleri Dergisi, 2021)
Aim: This study aims to evaluate parenting behaviours of mothers, living in the province of Bingol, in the postpartum period. Methods: The descriptive type research was conducted in a state hospital in the province of Bingol, between July and December, 2014. The study population consisted of mothers who meet the research inclusion criteria and gave birth in the studied hospital at the time of research. No sample selection was performed. The study was completed with 300 mothers. Data were collected by the researcher through face-to-face interview method using a "Questionnaire", and the "Postpartum Parenting Behaviour Scale (PPBS)". Results: In the study, the mothers in the 18-25 age group, mothers with a college or higher level of education, employed mothers, mothers having an income that exceeds their expenses, mothers having a nuclear family structure, mothers married for at least 1-5 years, mothers who gave birth for the first time, mothers who gave birth through a planned pregnancy, and mothers having pre-natal care for more than 10 times were found to have higher mean postpartum parenting behaviour scores (p<0.05). In the study, 2.3% of the mothers had 1 point in the PPBS, and 62.7% had scored full (6 points), and the average PPBS score of the mothers was found to be 5.27±1.17. Conclusion: In the study, it was found that the mean parenting scores of the mothers were higher; the mean PPBS scores was found to be affected by the age group, educational status, employment status, place of residence, income status, family type, duration of marriage, number of pregnancies, number of pre-natal cares, and whether the pregnancy was planned, whereas the mean PPBS scores was not found to be affected by the mode of delivery and gender of the baby.